A holistic design approach for 5th generation smart local energy systems: Project GreenSCIES. (1st March 2022) - Revesz, Akos; Dunham, Chris; Jones, Phil; Bond, Carole; Fenner, Russell; Mody, Sagar; Nijjhar, Rajvant; Marques, Catarina; Maidment, Graeme
Abstract: This paper introduces a project called GreenSCIES; an InnovateUK funded detailed design project to develop a Smart Local Energy System (SLES) delivering a significant carbon saving for local residents, schools and businesses. The SLES is centred around a 5th Generation District Heating and Cooling (5DHC) network in the London Borough of Islington. The local energy system will deliver low carbon heating, cooling, power and e-mobility charging powered by renewable energy and waste heat, sourced from the local area. The proposed SLES will manage and balance the supply, storage (both thermal and electrical) and use of local energy across mobility, power and heat vectors. It will do so using smart control technologies, bringing significant energy efficiency and security as well as social, environmental and economic benefits to Islington. The paper introduces the holistic SLES design approach developed by the GreenSCIES consortium, building upon an initial feasibility study previously published by the authors. The design methodology described takes technical and commercial aspects of a SLES design into account, whilst also explaining the importance of effective stakeholder engagement and co-design with local communities. The paper also provides a technical overview around the intended operation of ambient loop and heat pumps alongside long and short term thermal energy storage. A technical approach selected for integrating electric vehicles (EVs) and solar photovoltaic (PV) is also discussed in detail, alongside the control system architecture developed for the integrated SLES. The paper subsequently moves into demonstrating the benefits of the integrated SLES through a focused scheme design called New River, demonstrating integrated SLES performance compared to conventional systems in a real setting, through a comprehensive energy model. The results presented from a techno-economic analysis demonstrate that significant carbon savings and an attractive internal rate of return of (10%) can be achieved. The results presented show that even the smaller constructible "New River" scheme will save more 5000 tons of CO2 e annually. This is a reduction in carbon emissions by 80% over conventional systems and, therefore a major decarbonisation solution in large cities across the world. The GreenSCIES approach presented in this paper is replicable worldwide and could become a central part of delivering nations' net zero carbon strategy. Highlights: Ambient loops integrated with EV and PV could help decarbonise urban areas. Aquifer Thermal Energy Storage provides a novel way of balancing the system. The Behind the Meter electrical connection approach is cost-effective. Significant carbon savings and an attractive internal rate of return. The holistic SLES design approach is replicable and it can be used as a guide.